Pengembangan Model Pembelajaran Kooperatif Flip Tile Quiz Group Competition Dalam Blended Learning Untuk Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran Ekonomi - Nailariza Umami; Mila Faridatus Salma (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
This study aims to develop acooperative learnig model of Flip Tile Quiz Group Competition in mixed learning in economics subjects using research and development (RnD) methods and using research procedures according to Sugiyono. The research procedure according to Sugiyono used 4 steps consisting of potential and problems, data collection, product desaign, desaign validation. In order to determaine the feasibility of the resulting product design, namely through validation from material experts, language experts,and desaign experts. The data collection instrument used was a questionnaire with a likert scale from 1-5 with quantitative descriptive data analysis and percentages. The results of the reseach on the development of the FGC cooperative learning model are 80% of the material experts, 77.5% of linguists, 94% of design experts, and 79% of classroom teacher validation. Meanwhile, the results from the presentations of the three material, language, and design experts were 84.65%, which means they are in the very feasible category, the result of the response to student interest in learning obtained a percentage of 85% which is very good, can be used and increases student interest in learning. Based on the results of the validation by experts, the researchers can conclude the FGC learning model as a learning model that is feasible to use.